2006
DOI: 10.1152/ajpendo.00578.2005
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of ACTH stimulates expression of adrenal ACTH receptor and steroidogenic acute regulatory protein mRNA in fetal sheep

Abstract: -The late-gestation plasma cortisol surge in the sheep fetus is critical for stimulating organ development and parturition. Increased adrenal responsiveness is one of the key reasons for the surge; however, the underlying mechanisms are not fully understood. Our recent studies suggest that ACTH-mediated increased expression of ACTH receptor (ACTH-R) and steroid acute regulatory protein (StAR) may play a role in enhancing responsiveness. Hence, we examined effects of ACTH infusion in fetal sheep on mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
(58 reference statements)
2
8
1
Order By: Relevance
“…In agreement with previous studies (Le Roy et al 2000; Rehman et al 2007; Carey et al 2006; Su et al 2005; Johnston et al 2007; Mountjoy et al 1994), we found that the ACTH receptor-MC2R was significantly stimulated by ACTH incubation (12-fold). We also noticed a significant increase in MRAP mRNA level.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies (Le Roy et al 2000; Rehman et al 2007; Carey et al 2006; Su et al 2005; Johnston et al 2007; Mountjoy et al 1994), we found that the ACTH receptor-MC2R was significantly stimulated by ACTH incubation (12-fold). We also noticed a significant increase in MRAP mRNA level.…”
Section: Discussionsupporting
confidence: 93%
“…The acute response is mediated by the activity of the StAR protein, which leads to mobilization of cholesterol from cellular stores to the inner mitochondrial membrane where cholesterol side-chain cleavage (CYP11A1) is located (Fleury et al 1998; Ariyoshi et al 1998; Fleury et al 1996; Clark & Combs 1999; Lehoux et al 2003). Studies in fetal and adult adrenals across several species have shown that the chronic response of ACTH includes the activation of genes encoding the steroidogenic enzymes, HSD3B2, CYP21, CYP17, CYP11B1 (Neri et al 1991; Phillips et al 1996; Simmonds et al 2001; Bassett et al 2004; Schimmer et al 2006; Carey et al 2006; Coulter & Jaffe 1998; Di Blasio et al 1990; Galtier et al 1996; Lebrethon et al 1994; Mason et al 1993; Su et al 2005; Su & Rose 2008; Tangalakis et al 1990; Zhang et al 1999). These gene targets were confirmed in the current study in AA and FA cells using microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of ACTH to its cognate G protein-coupled receptor promotes the activation of protein kinase A and MAPK-dependent signaling cascades that collectively initiate adrenal-specific steroidogenic transcriptional programs [ 21 , 22 , 40 ]. Findings from numerous in vitro studies support the notion that ACTH is a positive regulator of ACTH-R mRNA expression [ 33 , 41 , 42 ]. More particularly, Winnay and Hammer [ 43 ] demonstrated in vitro that ACTH stimulation acutely activates the Mc2r gene promoter (i.e.…”
Section: Discussionmentioning
confidence: 72%
“…A large number of peptides like insulin [2], cyclosporine [3], corticotropin [4] are used for treating various diseases like diabetes and immunoregulatory disorders [57]. Owing to their immense therapeutic importance, peptides have been curated from literature and stored in form of databases such as Hemolytik [8], PhytAMP [9], APD2 [10], DAMPD [11], CAMP [12], YADAMP [13], CPPsite [14], TumorHoPe [15], Quorumpeps [16], Brainpeps [17], MilkAMP [18], DADP [19], LAMP [20] and AVPdb [21] to name a few.…”
Section: Introductionmentioning
confidence: 99%